Perilaku Pemilih Transpuan Kota Medan Pada Pemilihan Walikota Medan Tahun 2020 di Pelaksana Organisasi Persatuan Transpuan (Petrasu) - Haddad Nasution; Muryanto Amin; Tony P. Situmorang (PERSPEKTIF, 2023)
Based on the research problem questions above, the purpose of this research is to analyze the voting behavior of transwomen in the city of Medan and the factors that influence it in the 2020 Medan Mayor election using the voter behavior approach. The theory from Dennis Kavanagh, namely three models for analyzing voter behavior, namely sociological approaches, social psychology, and rational choices, were used to answer the research objectives. This type of research uses qualitative research methods, with a descriptive approach (description research). Data obtained from direct interviews in the field and library research. The results of the study stated that these transwomen formed their own associations because they felt alienated from other people in a community/organization. The tendency of the behavior of transwomen voters in the city of Medan in the 2020 Medan Mayor election shows a sociological voter behavior. This tendency was based on the fact that of all the informants who were successfully interviewed, almost all of them had the same preferences as friends or the community and their organizations.